2010
DOI: 10.1177/0741713610392765
|View full text |Cite
|
Sign up to set email alerts
|

The Connections Between Latino Ethnic Identity and Adult Experiences

Abstract: This study considers the influence of adult experiences on the development of Latino ethnic identity. Using purposeful and snowball sampling, adult participants responded to open-ended questions about their understanding of being Latino. Analysis indicated that changes in the environment or life circumstances had the greatest effect on the reevaluation of identity. This process, referred to as looping, occurred in 35% of the adults surveyed and illustrates the process that occurs when an individual questions p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…While most of the Latinas in the study reflected on how their early experiences impacted their current outlooks on life and/or ethnic identity, many also discussed marriage and motherhood as triggering evaluations or re-evaluations of ethnic identity. This process of re-evaluation of ethnic identity has also been seen among adult Latino men, but a change in the racial composition of the environment or a new job often triggers this evaluation (Torres et al 2012). In reference to these early experiences, many Latinas learned about their own culture and what is meant to be of Latino descent, but many also learned to be comfortable with people from cultures different from their own.…”
Section: Discussionmentioning
confidence: 96%
“…While most of the Latinas in the study reflected on how their early experiences impacted their current outlooks on life and/or ethnic identity, many also discussed marriage and motherhood as triggering evaluations or re-evaluations of ethnic identity. This process of re-evaluation of ethnic identity has also been seen among adult Latino men, but a change in the racial composition of the environment or a new job often triggers this evaluation (Torres et al 2012). In reference to these early experiences, many Latinas learned about their own culture and what is meant to be of Latino descent, but many also learned to be comfortable with people from cultures different from their own.…”
Section: Discussionmentioning
confidence: 96%
“…Given that racial and ethnic identities are socially constructed and variable for different individuals and communities rather than fixed (Haney Lopez, 1994;Torres et al, 2012;Z. Valdez, 2013), it is our responsibility as scholars to listen to the diverse needs of our Latinx community and to advance the conversation.…”
Section: Latinxmentioning
confidence: 99%
“…The only research that addressed ethnic identity change in adulthood was a study by Torres et al (2012). The findings of that study suggested that ethnic identity did change, and that it might change in adulthood when experiencing life changing or stressful circumstances.…”
mentioning
confidence: 99%